Rheological properties of wheat flour dough and pan bread with wheat bran. (September 2016) - Boita, Elis R.F.; Oro, Tatiana; Bressiani, Joseane; Santetti, Gabriela S.; Bertolin, Telma E.; Gutkoski, Luiz C.
Abstract: Wheat bran improves the nutritional properties of bread products due to the fiber content and antioxidant compounds, but causes changes in physical-chemical and technological properties. The objective of this study was to investigate the effect of wheat bran reincorporation in the dough properties and subsequent technological properties of breads. The dough and bread making properties were affected by the reincorporation of bran. Parameters such as mixing properties, viscosity, resistance to extension and extensibility demonstrated the influence of bran reincorporation into the gluten network. The presence of the bran also produced breads with lower specific volume, moisture, water activity and more hardness. The bran interactions with the gluten network are the main cause of the effects on dough quality, causing thinning and weakening of the gluten matrix. The flour presented different paste and hydration properties, affecting the rheology of the dough and performance in baking. Samples with 75% and 100% reincorporation were more nutrient-rich, providing enhanced functionality to the body, especially in relation to dietary fiber, but were responsible for more pronounced changes in the technological characteristics of the dough and breads. Highlights: The presence of bran resulted in increase in water absorption and weakened gluten network. The enhanced the moisture of breads is not sufficient for improve the texture of breads. The critical limit for the production of bread with added bran was 50%.